Clinical application of flexible and variable transparent endport technology in minimally invasive neuroendoscopic keyhole surgery: a practical new technology - Long Zhou; Shitao Mao; Can Wang; Huikai Zhang; Zhiyang Li; Minghui Lu; Wei Xia; Ping Song; Hui Ye; Jinjian Zhou; Zohaib Shafiq; Qianxue Chen; et al. (Scientific Reports)
Abstract With the development of endoscopic technology, neuroendoscopy utilizes its advantages such as good illumination, close range observation, and flexible degrees of freedom. Neuroendoscopic surgery can achieve advantages such as minimally invasive, high clearance rate, low incidence of complications, good brain tissue protection, and fewer surgery-related injuries. However, minimally invasive endoscopic surgery also has inherent limitations, since its narrow surgical channels are prone to collapse and require special instrument support. By summarizing the literature on the use of endoport technology in previous neuroendoscopic surgeries, and providing a detailed introduction and summary of our team’s newly developed simple variable endoport clinical experience, we analyzed the advantages, disadvantages, and precautions of flexible and variable transparent endport technology. After years of development and refinement, fixed endoport technology has been widely used in neuroendoscopic surgery, but it has certain shortcomings. Our team has developed a variable endoport system using simple and easily accessible materials. Although it has shortcomings in support, it provides good compensation for the flexibility of endport length and diameter, which is of great help for multi-instrument operation and bipolar electrocoagulation hemostasis, making surgical hemostasis more reliable. Meanwhile, the flexible and variable transparent endport system can be completely placed within the bone window, with significantly higher mobility than the hard endport system that cannot be completely placed below the bone window. The flexible and variable transparent endport system material is easy to obtain, manufacture, operate, and has extremely low cost, making it suitable for promotion and use in the vast majority of neurosurgery units, including primary hospitals.